An ESIPT-induced NIR fluorescent probe to visualize mitochondrial sulfur dioxide during oxidative stress in vivo. Issue 5 (21st December 2020) - Ren, Haixian; Huo, Fangjun; Wu, Xia; Liu, Xiaogang; Yin, Caixia
Abstract : An ESIPT-induced NIR fluorescent probe can visualize mitochondrial sulfur dioxide during oxidative stress in vivo . Abstract : Based on the change in electron distribution of the benzopyrylium unit before and after sulfite addition, a 2-(2′-hydroxyphenyl)benzothiazole (HBT)-based fluorophore generated the excited state intramolecular proton transfer (ESIPT) process with a near-infrared enhanced emission at 836 nm and a large Stokes shift (286 nm). The probe was applied to image SO2 derivatives in cells and mice. Our data will provide new ideas for the development of ESIPT-based fluorescence probe with longer wavelength emission.